The Literacy Movement in Creating a Smart and Healthy Young Generation (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Background: Pangkalpinang City faces two major challenges in its educational environment: a high incidence of violence against children and low levels of reading literacy. Although students at SDN 15 Pangkalpinang have achieved notable academic success, their motivation to read remains low, and exposure to violence poses a serious threat to their psychological well-being and academic development. Aims: This community service project aimed to cultivate a culture of literacy and enhance students’ motivation to read. Additionally, it sought to educate students, teachers, and parents on the psychological impacts of violence on children, to foster a healthier, safer, and more literate young generation. Method:The program was implemented in four phases: (1) Preparation, including needs assessment and coordination with school stakeholders; (2) Student Briefing, focusing on hygiene, health education, and literacy strategies; (3) Implementation, consisting of literacy counseling, group reading activities, health screenings, and handwashing education; and (4) Evaluation, utilizing pretest and posttest instruments to measure changes in students' reading motivation. Results: The intervention led to a significant increase in reading motivation among students. Pretest results showed 58% of students in the "weak" category. Following the program, 36% of students reached the "strong" category, and 8% achieved the "very strong" category. Health literacy activities improved students’ understanding of hygiene, while counseling sessions enhanced teachers' and parents' awareness of child protection and psychological well-being. Conclusion: The literacy movement positively impacted SDN 15 Pangkalpinang by improving students’ reading motivation and health literacy. It also successfully involved families and educators in creating a more supportive and protective school environment. The findings highlight the effectiveness of a collaborative, multi-stakeholder approach in addressing educational and psychological challenges among school-aged children.